2015
DOI: 10.1016/j.appet.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Training response inhibition to food is associated with weight loss and reduced energy intake

Abstract: The majority of adults in the UK and US are overweight or obese due to multiple factors including excess energy intake. Training people to inhibit simple motor responses (key presses) to high-energy density food pictures reduces intake in laboratory studies. We examined whether online response inhibition training reduced real-world food consumption and weight in a community sample of adults who were predominantly overweight or obese (N = 83). Participants were allocated in a randomised, double-blind design to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
354
4
20

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 232 publications
(395 citation statements)
references
References 60 publications
17
354
4
20
Order By: Relevance
“…Similarly, results for implicit attitudes were largely in favour of the null hypothesis (Rouder, Speckman, Sun, Morey, & Iverson, 2009). These results are inconsistent with our predictions based on previous studies that have revealed significant effects of inhibitory control training on food consumption (Allom et al., 2015, Houben, 2011, Houben and Jansen, 2011, Houben and Jansen, 2015, Lawrence et al., 2015a, Lawrence et al., 2015b, Veling et al., 2011). They are also in disagreement with predictions based on other studies showing effects of alcohol-related go/no-go training on implicit attitudes towards alcohol (Houben et al., 2011, Houben et al., 2012a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, results for implicit attitudes were largely in favour of the null hypothesis (Rouder, Speckman, Sun, Morey, & Iverson, 2009). These results are inconsistent with our predictions based on previous studies that have revealed significant effects of inhibitory control training on food consumption (Allom et al., 2015, Houben, 2011, Houben and Jansen, 2011, Houben and Jansen, 2015, Lawrence et al., 2015a, Lawrence et al., 2015b, Veling et al., 2011). They are also in disagreement with predictions based on other studies showing effects of alcohol-related go/no-go training on implicit attitudes towards alcohol (Houben et al., 2011, Houben et al., 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Our stop-signal training task had an overall stop-signal rate of 25%, and paired a target food, chocolate, with signals on 87.5% of trials. However, the inclusion of inter-block feedback to ensure that training placed demands on action cancellation, as opposed to action restraint (Eagle et al., 2008, Schachar et al., 2007; see above), is likely to have decreased the rate of successful inhibition (70%) compared with other training tasks where the rate of inhibition was much higher (average ∼92%; Houben, 2011, Houben and Jansen, 2011, Houben and Jansen, 2015, Lawrence et al., 2015a, Lawrence et al., 2015b, Veling et al., 2011). In a recent study Forman et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Revealingly, many of these dopamine-dependent cognitive functions have been identified as risk factors for overeating [100102], and even targets for behavioral interventions for obesity [103,104]. As such, pre-existing and/or diet-induced alterations in dopamine signaling may produce impairments in executive function, which may increase susceptibility for overeating and weight gain.…”
Section: Neural Adaptations In the Dorsal Striatummentioning
confidence: 99%